Pengaruh Konseling Kelompok Dengan Teknik Self Management Terhadap Peningkatan Identitas Diri Siswa - Annas Yudi Ardani; Purwati Purwati; Astiwi Kurniati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this study is to see how group counseling with self-management approaches affects self-identity in students in class VIII D at SMP N 1 Kranggan. This is a quantitative research method. Experimental research is the name given to this type of study. A pre-experimental one group pretest posttest was used in this study's design. SMP N 1 Kranggan Kab. Temanggung in class VIII D hosted the implementation of this study. The participants in this study were eight eighth-grade students from SMP N 1 Kranggan who had a low sense of self-identity. Using a questionnaire as a data collection tool. A posttest was given to 8 students who had a low level of self-identity and were given group counseling treatment using the Self Management technique. The Paired Sample T-test was then used to test the results. The significance results show that 0.123 is greater than 0.05, indicating that Ho is accepted and Ha is rejected, indicating that group counseling with Self Management techniques has an effect on increasing students' self-identity after treatment with Self Management techniques.